Predictors of poor mental health among nurses during COVID‐19 pandemic - Son Chae Kim; Carlota Quiban; Christine Sloan; Anna Montejano (Wiley, 2021)
Abstract Aims To examine the impact of various factors affecting nurses' mental health during the COVID‐19 pandemic. Design An online cross‐sectional study. Methods Registered nurses who graduated from a nursing school in Southern California, USA, participated in the study from 20 April-10 May 2020 (N = 320). Kendall's tau correlations and multivariate logistic regression procedures were performed with stress, anxiety and depression as outcome variables. Results Most nurses reported moderate/high stress (80.1%), while 43% and 26% reported moderate/severe anxiety and depression, respectively. COVID‐19 patient care was positively associated with moderate/severe high stress (OR = 2.25; p = .012) and moderate/severe anxiety (OR = 3.04; p < .001), whereas quarantine was associated with moderate/severe depression (OR = 2.68; p < .001). High levels of family functioning, resilience and spirituality predicted two‐ to sixfold lower odds of moderate/severe stress, anxiety or depression. High resilience, spirituality and family functioning appear to be good coping mechanisms for nurses against stress, anxiety and depression during the pandemic.